Analisis Pengaruh Kualitas Layanan Terhadap Kepuasan Pengguna Aplikasi MyARS Menggunakan Metode Webqual 4.0 - Arey DS; Rangga Sanjaya (Universitas Nusa Cendana, 2021)
Submission of ongoing academic activities and information in the field of education can take advantage of information technology. One of the most important is to create an academic information system that can be accessed by students online. The MyARS application is an academic information system that provides lecture information for ARS University students. The MyARS application page can be accessed via the link https://myars.ars.ac.id/. The question related to this research is whether the quality of the MyARS application used has an impact on user satisfaction. This study focuses on user satisfaction with the webqual method which consists of three variables, namely usability, information quality, and interaction quality. The obtained data is processed using multiple linear regression analysis techniques using SPSS 16 software. the quality of information is 3,620 with a percentage level of 83.79%. This is also supported by the regression results which prove the quality of usability has a significant positive effect on customer satisfaction. The results of the information quality score of 4,051 with a percentage level of 83.35%. This is also supported by the regression results which prove the quality of information has a significant positive effect on customer satisfaction. While the results of the information quality score of 2,167 with a percentage level of 80.25% This is also supported by the regression results which prove that the quality of information has a significant positive effect on customer satisfaction